“Resistiéndose al poder y a la dirección”: La hija del rey de España, de Teresa Deevy, como una llamada feminista a la acción”. - Úna Kealy (Estudios Irlandeses, 2020)
Born in 1894, into a middle-class family with nationalist sympathies, Teresa Deevy was the youngest of thirteen children whose father died when she was two years old. Her mother prioritised her daughters’ education and Teresa boarded in the Ursuline Convent a short distance from her home, taught by a community of Catholic sisters with one hundred years’ experience in educating young women. St. Ursula’s Annual (1911) to which Deevy contributed, reveals a formal and informal curriculum of music, sport, dramatic, critical and journalistic writing, and debating. A debate in 1911 asked audience and participants to consider whether women should have equal social and political rights with men (St. Ursula’s Annual 10) while a series of guest lecturers to the school that year, gave lectures on Sheridan Le Fanu, approaches to studying history, the development of Irish music, Saint Bridget and, the genre of the passion play (St. Ursula’s Annual 34). Regular school trips to musical recitals and concerts in the city occurred and students were encouraged to write and perform original plays. In an article entitled “Books We Have Read” Deevy’s love of literature emanates from her reflections on the books she and her friends read that school year. Leeney references Deevy’s contributions to the annual as evidence of an “optimistic, energetic and intellectually alive” (Irish Women Playwrights 161) young woman while O’Doherty asserts that they attest to an “infectious ebullience” (“Wife” 25). One can add that the prioritisation of social, cultural and intellectual concerns and the development of practical skills, evident within the activities described within the annual, provided the intellectual groundwork and commitment towards social and political activism that is manifested within The King of Spain’s Daughter.